On Cicero’s De domo. A survey of recent work - Scheidegger-Lämmle, Cédric (Ciceroniana On Line, 2017)
The contribution offers a brief survey of research on De domo and locates it in the changing landscape of Ciceronian studies. After a consideration of the old debate on the speech’s authenticity, it identifies four dominant lines of inquiry in recent scholarship on De domo. Il contributo offre una breve prospettiva di ricerca sul De domo di Cicerone, collocando l’orazione nel panorama in continua trasformazione degli studi ciceroniani. Dopo una riflessione sullo storico dibattito riguardante l’autenticità del dialogo, si identificano quattro campi di ricerca dominanti nella critica recente al De domo.